Pengaruh Pengetahuan dan Motivasi Mahasiswa Akuntansi Terhadap Minat Mahasiswa Berkarir di Bidang Perpajakan (Studi Kasus Mahasiswa di Sekolah Tinggi Bisnis dan Manajemen Dua Sudara Bitung dan Sekolah Tinggi Ilmu Ekonomi Petra Bitung) - Mecky Wurangian; Ninda Rahmawati Arifin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the influence of knowledge and motivation on accounting students' interest in choosing a career in taxation. The case study was conducted on students of the Accounting Study Program, Dua Saudara Bitung College of Business and Management and Petra Bitung College of Economics. The low interest of students in pursuing a career in taxation is often caused by a lack of knowledge about taxation and existing job opportunities. This study uses a quantitative approach with a survey method through a questionnaire. The results of this study are that Tax Knowledge (X1) has a significant and positive influence on Career Interest in Taxation (Y). This can be seen from the calculated t value of 4.157 which is greater than the t table (1.66543) and a very small significance value (0.000 0.05). Motivation (X2) has a significant and positive influence on Career Interest in Taxation (Y). The t-value for motivation is 3.059, which is greater than the t-table (1.66543), with a significance value of 0.003 0.05. It is concluded that both Tax Knowledge (X1) and Motivation (X2) have a significant influence on Career Interest in Taxation (Y) at the Bitung Dua Sudara Business and Management College and the Bitung Petra College of Economics. This shows that to increase career interest in taxation, it is important to develop knowledge and motivation related to the field. These two variables positively influence an individual's desire to pursue a career in the taxation profession.